Study of the dynamics of aerosol optical thickness in Perú and South America from images MODIS onboard the AQUA and TERRA satellites in 2000-2013 period - Rojas Benavente, Noelia (2015)
The aim of this work is to study the dynamics of aerosols in Peru and South America at latitude 4°N-24°S and at longitude 83°W-33°W, from monthly averages images Aerosol Optical Thickness, AOT, at 550 nm wavelength measured by the Moderate Resolution Imaging Spectroradiometer, MODIS, sensor onboard the TERRA and AQUA satellites for a period of fourteen years, from 2000 to 2013. The AOT data in-situ in 6 AERONET stations of South America that includes four from Brazil, such as, Rio Branco, Paraná Ji, Alta Foresta, and Campo Grande; from Chile, the Arica station and from Bolivia, La Paz station, and 166 AOT-MODIS-TERRA data images from the monthly products obtained during the period 2000 to 2013, and 138 AOT-MODIS-AQUA data images from the monthly products obtained during the period 2002 to 2013 which was estimated using the Giovanni Web-based online visualization and analysis tool with a 1°×1° resolution, i.e., 110 km×110 km. The AOT-MODIS-TERRA time series have maximum and minimum values from 0.0 to 0.499, taking their maximum values in the dry season of South Hemisphere between August to November for 14 years. The AOT-MODIS-AQUA time series have maximum and minimum values from 0.0 to 0.493, taking their maximum values in the dry season during the 12 years. The AOT-AERONET time series from Brazil four stations shows a seasonal variation with peaks in the dry season for 14 years, meanwhile, from Chile and Bolivia stations shows a very different seasonal variation AOT/MODIS data, having few records of AOT data. The scatter plots of AOT-MODIS-vs-AOT-AERONET time series show a high correlation from 0.8 to 0.9 at four stations in Brazil and low correlation, 0.33-0.39 in the Chile station and 0.13-0.19 in the Bolivia station.